Penentuan Kadar Flavonoid Total dalam Ekstrak Etanol Buah Renggak (Amomum dealbatum Roxb.) Menggunakan Spektrofotometri UV–Vis - Lalu Ardian Hadi; Rizqa Fersiyana Deccati; Handa Muliasari; Nisa Isneni Hanifa (Acta Chimica Asiana, 2026)
The local plant, Amomum dealbatum Roxb. (A. dealbatum), is native to Lombok Island. This plant is a member of the Zingiberaceae family, which is recognised to have antifungal and antibacterial properties due to the presence of secondary metabolites, particularly flavonoids. Nevertheless, there is still little information and few reports regarding the overall flavonoid content of A. dealbatum fruit. As a chemical marker to support an extract’s quality control and pharmacological effects, Total Flavonoid Content (TFC) determination is crucial. The purpose of this work was to use UV-Vis spectrophotometry to measure the TFC in the ethanol extract of A. dealbatum fruit. Using a 1:10 solvent: simplicia ratio and maceration with 96% ethanol, the extraction procedure was completed. Thin Layer Chromatography (TLC) and the Wilstatter test were then used to identify the extracted material qualitatively. Using a UV-Vis spectrophotometer and a colourimetric approach, TFC was measured. The ethanol extract of A. dealbatum fruit contained flavonoids, as indicated by the qualitative analysis. The TFC values were 3.0833 ± 0.1439 mg rutin equivalent (RE)/g extract and 0.4858 ± 0.0014 mg quercetin equivalent (QE)/g extract. These findings suggest that the ethanol extract of A. dealbatum contains more flavonoid glycosides than flavonoid aglycones. This finding shows potential for further development. As this study is still limited to TFC at the extract level, further research on TFC at the fraction, sub-fraction, and isolate levels is needed to obtain more specific information about the active compounds contributing to its biological activities. In addition, further pharmacological testing is required to confirm the therapeutic potential of A. dealbatum and support its development as a candidate raw material for traditional medicine industries.